Long-term trends in the Oxford knee score following total knee replacement. - Williams, D; Blakey, C; Hadfield, S; Murray, D; Price, A; Field, R (2013)
The Oxford knee score (OKS) is a validated and widely accepted disease-specific patient-reported outcome measure, but there is limited evidence regarding any long-term trends in the score. We reviewed 5600 individual OKS questionnaires (1547 patients) from a prospectively-collected knee replacement database, to determine the trends in OKS over a ten-year period following total knee replacement. The mean OKS pre-operatively was 19.5 (95% confidence interval (CI) 18.8 to 20.2). The maximum post-operative OKS was observed at two years (mean score 34.4 (95% CI 33.7 to 35.2)), following which a gradual but significant decline was observed through to the ten-year assessment (mean score 30.1 (95% CI 29.1 to 31.1)) (p < 0.001). A similar trend was observed for most of the individual OKS components (p < 0.001). Kneeling ability initially improved in the first year but was then followed by rapid deterioration (p < 0.001). Pain severity exhibited the greatest improvement, although residual pain was reported in over two-thirds of patients post-operatively, and peak improvement in the night pain component did not occur until year four. Post-operative OKS was lower for women (p < 0.001), those aged < 60 years (p < 0.003) and those with a body mass index > 35 kg/m(2) (p < 0.014), although similar changes in scores were observed. This information may assist surgeons in advising patients of their expected outcomes, as well as providing a comparative benchmark for evaluating longer-term outcomes following knee replacement.